Introduction of hybrid rice cultivation: A boost on rice productivity and livelihood security of farmers - Mukherjee, Pijush Kanti; Dubey, R. P.; Choudhary, V. K.; Chethan, C. R.; Gharde, Yogita; Singh, P. K.; Pawar, Deepak Vishwanath; Sreekanth, Dasari; A., Jamaludheen; Dubey, Jitendra Kumar; Raghuwanshi, Monika (Indian Farming, 2025)
The Farmer FIRST Programme (FFP) of ICAR-Directorate of Weed Research, Jabalpur, was initiated in 2017 in Barauda and Umariya Choubey villages of Panagar block, Jabalpur district, Madhya Pradesh, to enhance rice productivity and farmers' livelihoods through the introduction of hybrid rice cultivation and improved weed management practices. Initially, the entire rice area in these villages was under the traditional, long-duration variety ‘Kranti’, which limited productivity and delayed wheat sowing. Through participatory interventions, high-yielding hybrid rice varieties i.e. ‘Arize Gold 6444’ and ‘Ganga Hybrid’ were introduced, coupled with the use of broad-spectrum, high potency, low dose ready-mix herbicides in rotation and robust capacity-building efforts. As a result, hybrid rice adoption expanded to over 99% of the rice area in both villages by 2023–24. Over seven years, grain yield increased by 33–34%, and net returns improved by 62–65% compared to traditional farmers’ practices. The sustained adoption of these technologies, even after the project transitioned to a new site, highlights the long-term positive impact of the programme on productivity and profitability in rice cultivation.